Enhanced FnCas12a-Mediated Targeted Mutagenesis Using crRNA With Altered Target Length in Rice - Negishi, Katsuya; Mikami, Masafumi; Toki, Seiichi; Endo, Masaki (Frontiers in Genome Editing, 2020)
The CRISPR/Cas12a (Cpf1) system utilizes a thymidine-rich protospacer adjacent motif (PAM) and generates DNA ends with a 5´ overhang. These properties differ from those of CRISPR/Cas9, making Cas12a an attractive alternative in the CRISPR toolbox. However, mutation efficiencies of Cas12a orthologs are generally lower than those of SpCas9, and depend on their target sequences. Here, we report that the efficiency of FnCas12a-mediated targeted mutagenesis varies depending on the length of the crRNA guide sequence. Generally, the crRNA of FnCas12a contains a 24-nt guide sequence; however, some target sites showed higher mutation efficiency when using crRNA with an 18-nt or 30-nt guide sequence. We also show that a short crRNA containing an 18-nt guide sequence could induce large deletions compared with middle- (24-nt guide sequence) and long- (30-nt guide sequence) crRNAs. We demonstrate that alteration of crRNA guide sequence length does not change the rate of off-target mutation of FnCas12a. Our results indicate that efficiency and deletion size of FnCas12a-mediated targeted mutagenesis in rice can be fine-tuned using crRNAs with appropriate guide sequences.